A COMPARATIVE STUDY OF HEAVY METAL CONCENTRATIONS IN Nerita lineata FROM THE INTERTIDAL ZONE BETWEEN DUMAI INDONESIA AND JOHOR MALAYSIA - Bintal Amin; Ahmad Ismail; Aziz Arshad; Che Kong Yap; M Salleh Kamarudin (JOURNAL OF COASTAL DEVELOPMENT, 2006)
The concentrations of Cd, Cu, Pb, Zn, Ni and Fe were determined in the marine gastropod Nerita lineata collected on May 2005 from the intertidal zone of fourteen stations in Dumai, Indonesia (mean length 21.43 – 24.04 mm) and ten stations in Johor, Peninsular Malaysia (mean length 22.61 – 26.60 mm). The results of the present study showed that metal concentrations in the shell, operculum and soft tissue of N. lineata varied at different sampling stations. The mean concentrations of Cd, Cu, Pb, Zn, Ni and Fe in the samples collected from Dumai were 4.14; 5.90; 44.43; 3.74; 20.73; 24.91 μg/g in shell; 4.16; 7.31; 51.78; 17.63; 23.52; 30.60 μg/g in operculum and 0.71; 15.16; 9.34; 94.69; 5.08; 397.96 μg/g dry weight in the total soft tissue; whilst those collected from Johor were 4.18; 5.06; 59.84; 4.8122; 19.29; 31.60 μg/g in shell; 4.73; 6.51; 60.57; 19.48; 20.68; 34.92 μg/g in operculum and 1.24; 18.02; 19.75; 95.09; 5.57; 473.56 μg/g dry weight in the total soft tissue, respectively. Samples of N. lineata from both Dumai and Johor tend to show similar trend in metal accumulation in which the concentrations of Cd, Pb and Ni decreased in the order: operculum > shell > soft tissue whilst Cu, Zn and Fe in the order of soft tissue > operculum > shell. In general, samples from Johor accumulated higher heavy metal concentrations when compared to samples from Dumai, except for Cu and Ni in the shell and operculum, which exhibited vice versa situation. Higher concentrations of metals were recorded in samples collected from the stations close to the industrial and anthropogenic activities. However, most of the concentrations were still comparable to the previous reported studies from other geographical areas.